The arms race between heliconiine butterflies and Passiflora plants – new insights on an ancient subject - de Castro, Érika C. P.; Zagrobelny, Mika; Cardoso, Márcio Z.; Bak, Søren (Biological reviews of the Cambridge Philosophical Society, 2018)
ABSTRACT Heliconiines are called passion vine butterflies because they feed exclusively on Passiflora plants during the larval stage. Many features of Passiflora and heliconiines indicate that they have radiated and speciated in association with each other, and therefore this model system was one of the first examples used to exemplify coevolution theory. Three major adaptations of Passiflora plants supported arguments in favour of their coevolution with heliconiines: unusual variation of leaf shape within the genus; the occurrence of yellow structures mimicking heliconiine eggs; and their extensive diversity of defence compounds called cyanogenic glucosides. However, the protection systems of Passiflora plants go beyond these three features. Trichomes, mimicry of pathogen infection through variegation, and production of extrafloral nectar to attract ants and other predators of their herbivores, are morphological defences reported in this plant genus. Moreover, Passiflora plants are well protected chemically, not only by cyanogenic glucosides, but also by other compounds such as alkaloids, flavonoids, saponins, tannins and phenolics. Heliconiines can synthesize cyanogenic glucosides themselves, and their ability to handle these compounds was probably one of the most crucial adaptations that allowed the ancestor of these butterflies to feed on Passiflora plants. Indeed, it has been shown that Heliconius larvae can sequester cyanogenic glucosides and alkaloids from their host plants and utilize them for their own benefit. Recently, it was discovered that Heliconius adults have highly accurate visual and chemosensory systems, and the expansion of brain structures that can process such information allows them to memorize shapes and display elaborate pre‐oviposition behaviour in order to defeat visual barriers evolved by Passiflora species. Even though the heliconiine–Passiflora model system has been intensively studied, the forces driving host‐plant preference in these butterflies remain unclear. New studies have shown that host‐plant preference seems to be genetically controlled, but in many species there is some plasticity in this choice and preferences can even be induced. Although much knowledge regarding the coevolution of Passiflora plants and heliconiine butterflies has accumulated in recent decades, there remain many exciting unanswered questions concerning this model system.